Videogames-as-a-service: converting freemium- to paying-users through pop-up advertisement value - Hussain, A. (Emerald Group Holdings Ltd., 2021)
Purpose: Though the videogame literature is thriving, little remains known regarding the effectiveness of pop-up ads that appear in videogames. Addressing this gap, this study, therefore, aims to explore pop-up ads as an important tool to prompt gamer-perceived advertisement value and their subsequent intent to install the advertised videogame. Design/methodology/approach: To frame the analyses, the authors adopt and extend Ducoffeâs advertising value model by incorporating the visual/audio aesthetic videogame components that are largely overlooked in prior research. Using a self-administered survey, data were collected from 321 online gamers. The authors tested the model by using partial-least-squares-based structural equation modeling (PLS-SEM). Findings: The results indicate that pop-up ad-related incentives, entertainment, credibility, personalization, audio aesthetics and irritation significantly affect user-perceived ad value. In turn, perceived ad value was found to affect playersâ intent to install the advertised videogame. Research limitations/implications: Though the findings corroborate the importance of pop-up ads being perceived as informative and/or entertaining, they also emphasize the value of personalized ads, ad-related incentives and audio aesthetic, which impact gamersâ intent to install the advertised videogame. Practical implications: This study advances managerial understanding of videogame-based services, which is expected to be particularly useful for freemium-based videogame marketers and developers. Originality/value: By extending Ducoffeâs model of advertising value, the authors apply the proposed framework in the online videogaming-based pop-up ad context, and explore the effect of user-perceived pop-up ad value on their intent to install the advertised videogame. Â© 2021, Emerald Publishing Limited.